2011
DOI: 10.1123/ijsnem.21.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Does Caffeine Added to Carbohydrate Provide Additional Ergogenic Benefit for Endurance?

Abstract: Context: Carbohydrate (CHO) and caffeine (CAF) both improve endurance performance. Purpose: To determine by systematic literature review coupled with meta-analysis whether CAF ingested with CHO (CHO+CAF) improves endurance performance more than CHO alone. Methods: Databases were searched using the keywords caffeine, endurance, exercise, carbohydrate, and performance. Criteria for inclusion were studies that used human subjects performing an endurance-exercise performance task and included both a CHO and CHO+CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 82 publications
(139 reference statements)
3
41
1
2
Order By: Relevance
“…Effect sizes (ES) were calculated using a random-effects model that accounts for true variation in effects occurring from study to study, as well as random error within single studies. This random effects model was preferred over a fixed-effect approach as some experimental parameters such as the measurement of EI had wide variation, which is better considered with the random-effects model 195 during analysis (14). Since only one of the included studies reported relative EI, and none provided results for EE, only absolute energy intake was considered in the meta-analysis.…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect sizes (ES) were calculated using a random-effects model that accounts for true variation in effects occurring from study to study, as well as random error within single studies. This random effects model was preferred over a fixed-effect approach as some experimental parameters such as the measurement of EI had wide variation, which is better considered with the random-effects model 195 during analysis (14). Since only one of the included studies reported relative EI, and none provided results for EE, only absolute energy intake was considered in the meta-analysis.…”
Section: Meta-analysis Proceduresmentioning
confidence: 99%
“…Subgroup meta-analysis and/or meta-regression were also performed to test whether differences in methodologies could explain the variation in ES between trials (14,18). This analysis included metaregressions of EI as a continuous variable and sub-group meta-analyses were conducted for categorical data such as exercise intensity and body mass status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic literature review examined the benefi t of co-ingestion of caffeine and carbohydrate ingestion on enduranceexercise performance [ 197 ]. Criteria for inclusion were studies that used human subjects performing an endurance-exercise performance task and included both a carbohydrate and carbohydrate-caffeine condition.…”
Section: Combinations That Enhance Aerobic/anaerobic Performancementioning
confidence: 99%
“…Caffeine can stimulate the central nervous system, reduce fatigue, stimulate mental activity, improve athletic performance, endurance, and reduce errors caused by workers because of tiredness [5,8,26]. On the other hand, high doses of caffeine can affect coordination, which leads to a poorer than expected athletic performance [36].…”
mentioning
confidence: 99%